Penser l’apport du care à l’évaluation et à la gestion des pratiques enseignantes - Manon Bouchareu (Éducation et Socialisation)
This research aims to show how the French educational policy, that wants achieve equality and democracy, should focus on vulnerability of its subjects and on their interdependence. Following an earlier dissertation on gender studies, we assert that care ethics may revitalize educators’ empowerment, although it’s an underrated reference field by the school system. This article is based on an analogy with a paper written by Pascale Molinier on the limit of managing hospital as if it was an airport. It proposes to investigate the similarities between the management methods in hospital and school settings. It attempts to demonstrate two ideas: first, combine “new public management” and attentiveness is challenging for the institution and its agents; but then it is nevertheless essential to reach integrate these seemingly contradictory logics. This is all the more essential for the development of an educational act referred to the emancipation of relational subjects: students as well as teachers.